2020
DOI: 10.1037/bul0000228
|View full text |Cite
|
Sign up to set email alerts
|

Fear of pain and pain intensity: Meta-analysis and systematic review.

Abstract: The fear avoidance model (FAM) represents a cognitive–behavioral explanatory approach for pain chronification. The core assumption is that fear of pain (FOP) following an acute pain experience facilitates the development of pain chronification, disability, and receding functionality. Thus, the model predicts a positive association between FOP and pain intensity in pain patients, which was frequently investigated; however, results were inconsistent. To highlight inconsistencies, we performed integrative statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 241 publications
(399 reference statements)
6
29
2
1
Order By: Relevance
“…According to the theory in the neurophysiology of pain, the individual's psychological state, anxiety, stress, and fears can activate pain stimuli and lead to the perception of pain ( Cimpean & David, 2019 ). In other words, negative pain experiences in the past can also open the gate and pain impulses pass through when the gate is open and cause intense pain ( Markfelder & Pauli, 2020 ). Fear of pain is related to the past painful experiences of the individual, and especially recurrent and unmanageable pain experiences may lead to the development of pain fear ( Cimpean & David, 2019 ).…”
mentioning
confidence: 99%
“…According to the theory in the neurophysiology of pain, the individual's psychological state, anxiety, stress, and fears can activate pain stimuli and lead to the perception of pain ( Cimpean & David, 2019 ). In other words, negative pain experiences in the past can also open the gate and pain impulses pass through when the gate is open and cause intense pain ( Markfelder & Pauli, 2020 ). Fear of pain is related to the past painful experiences of the individual, and especially recurrent and unmanageable pain experiences may lead to the development of pain fear ( Cimpean & David, 2019 ).…”
mentioning
confidence: 99%
“…The age also affects the pain level, but the effect size is very low as the odds are close to 1. The literature says that pain might be due to fear ( Crombez et al, 2013 ; Markfelder & Pauli, 2020 ). Fear of pain aggravates the feeling of pain ( Crombez et al, 2013 ), and this study found the same on COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 With higher FOP when experiencing painful events, nonclinical patients may report higher pain degrees, 3 whereas chronic patients may report more pain density, worse activity performance and lower quality of life. 4,5 To assess FOP in the pain population, professor McNeil developed the fear of pain questionnaire-III (FOP-III) 6 in 1998, which has been widely validated in many different countries, including China, 7 Portugal, 8 Turkey, 9 Dutch, 10 Italy, 11 and Brazil, 12 and exhibited excellent reliability and validity in various cultures. Although it has been confirmed applicable to evaluating not only trait FOP but also state FOP in nonclinical 13 and clinical people, 14 FOP-III is still not brief enough for the administration of patients in busy outpatient and inpatient settings.…”
Section: Introductionmentioning
confidence: 99%